Introduction to programming with Java a problem solving approach - Dean, John 1962-; Dean, Ray 1936- (McGraw-Hill, 2014)
Teaches the reader how to write programs using Java. This book transitions smoothly through a carefully selected set of procedural programming fundamentals to object-oriented fundamentals. During this early transition and beyond, it emphasizes problem solving